A Study of Variation in Adult Thrombocytopenic Histograms: A Graph Often Overlooked - Shetty, Archana; V, Shubha H; Chowdappa, Vijaya; G, Vivek T (Annals of Pathology and Laboratory Medicine, 2020)
Background: With the advent of automation in hematology, both platelet indices and their histograms are available from the blood cell counters at no extra cost or time. The variations of histograms in various mechanisms of thrombocytopenias are explored in this study. Methods: Adults with thrombocytopenia determined with (name of the analyser) were categorized into four groups based on the mechanism of thrombocytopenia and variations in platelet histograms were studied in all groups. Data was collated and analysed using Excel. Results: A total of 224 adults with thrombocytopenia were seen, most of them had hyperdestructive type (73.6%) followed by hypoproductive type (16.08%), abnormal pooling (6.3%) and EDTA induced thrombocytopenia (4.01%). The following variations in histogram were seen; Normal curve (8.03%), Curve not touching/reaching the baseline (43.75%), Broad based curve (10.71%), Bimodal curve (7.14%), Curve with short peak (25.9%) and Saw-tooth appearance of curve (4.47%) and correlated with the above mentioned mechanisms of thrombocytopenias using SPSS software version 20. Conclusion: An awareness regarding the variations in the platelet curve ensures a good correlation with its numerical parameters and also with the etiology of thrombocytopenias. With the era of automation taking over in most of the laboratories, it is imperative to have knowledge about these simple yet, often overlooked platelet histograms.